2018
DOI: 10.1159/000477400
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Wealth and Religion on the Ownership of Captive Lemurs in Madagascar Using Qualitative and Quantitative Data

Abstract: Primates are kept as pets for various reasons including as indicators of wealth. Ownership of primates can also be influenced by religion. In Madagascar, thousands of lemurs are kept as pets, but the roles of wealth and religion in the ownership of captive lemurs have not been explored. We use quantitative and qualitative data to examine these aspects of ownership. Quantitative data were collected (July to August 2016) in households (n = 596) of 12 urban and rural towns in Madagascar using semi-structured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…We also found that, while population density and unemployment rate significantly correlated with trade dynamics, they had very low explanatory power and are therefore likely to have less influence on trade dynamics compared to species traits and trade regulation. By contrast, consumers in other pet markets are known to either have higher disposable incomes compared with non-consumers (Alves et al 2019), or associate pet ownership with wealthy status (Reuter et al 2018). Norconk et al (2020);and Bennett et al (2021) suggest that wealth inequality (i.e., relative wealth), rather than absolute wealth, is a driver for both the harvesting and consumption of wildlife, including live pets.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, while population density and unemployment rate significantly correlated with trade dynamics, they had very low explanatory power and are therefore likely to have less influence on trade dynamics compared to species traits and trade regulation. By contrast, consumers in other pet markets are known to either have higher disposable incomes compared with non-consumers (Alves et al 2019), or associate pet ownership with wealthy status (Reuter et al 2018). Norconk et al (2020);and Bennett et al (2021) suggest that wealth inequality (i.e., relative wealth), rather than absolute wealth, is a driver for both the harvesting and consumption of wildlife, including live pets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in 2016, a short clip of a habituated ring-tailed lemur Lemur catta was circulated, reaching over 20 million viewers within a few weeks. This post similarly led to a marked increase in search trends for 'lemurs' but also to an increase in direct references to 'wanting a lemur' pet (Clarke et al 2019; see also Reuter et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We show here, the unintentional sharing of images/video featuring lemurs in non-natural settings and close to humans, can have indirect impacts on how English-speaking people perceive these wild animals. This may also be the case in Madagascar, where there is already published anecdotal evidence that ‘selfies’ posted with pet lemurs (often on Facebook) can show wealth or are considered ‘cool’ [55]. Therefore, any conservationists, primatologists, and/or non-governmental organizations (NGOs) should be aware of this context when they put information about lemurs on social media, as there is the risk that the information is misperceived both by English and non-English speaking audiences.…”
Section: Discussionmentioning
confidence: 99%